Beyond the academy: lived Asian public theology of religions - Moe, David Thang (Princeton theological monograph series, 2024)
"The term 'public theology' was introduced by Martin E. Marty in a 1974 article. Since then, scholarly discussions on public theology have become more popular in academic circles. This book, however, is about the invitation for moving beyond the academy. It provides two reasons for doing so. First, an overtly academic public theology is in crisis today. Although public theology may be flourishing in the academy, its relevance for real life is limited. Second, there is the 'ecclesial flourishing' among grassroots Christian communities across Asia who witness to their lived faith in public and hidden life. Their voices are largely unheard due to the gaps between the academy and the church. This volume argues that we should consider their voices as key sources for developing a relevant lived Asian public theology. The author makes the case for reimagining the paradigm shifts in lived Asian public theology of religions and for bridging the unhappy gaps between the academic and grassroots voices." --